Study of Art Plaza Circulation Theory and Shape of Art Plaza - Imam Firmansyah (Journal La Multiapp, 2020)
The circulation system is a vital linking infrastructure that connects various activities and uses land on an area and inside a building that considers functional, economic, flexibility and comfort aspects. The explanation of this theory emphasizes the uniqueness of the building itself. So that there are various shapes of buildings in an effort to adjust to environmental conditions, climate, and natural surroundings. As a result, the resulting building has a special shapeation in accordance with the idea of an architect.